Expression of Immune Related Genes and Possible Regulatory Mechanisms in Alzheimer’s Disease - Lu, Yanjun; Li, Ke; Hu, Yu; Wang, Xiong (Frontiers in immunology, 2021)
Immune infiltration of peripheral natural killer (NK) cells in the brain has been observed in Alzheimer’s disease (AD). Immunity-related genes (IRGs) play an essential role in immune infiltration; however, the expression of IRGs and possible regulatory mechanisms involved in AD remain unclear. The peripheral blood mononuclear cells (PBMCs) single-cell RNA (scRNA) sequencing data from patients with AD were analyzed and PBMCs obtained from the ImmPort database were screened for cluster marker genes. IRG activity was calculated using the AUCell package. A bulk sequencing dataset of AD brain tissues was analyzed to explore common IRGs between PBMCs and the brain. Relevant regulatory transcription factors (TFs) were identified from the Human TFDB database. The protein-protein interaction network of key TFs were generated using the STRING database. Eight clusters were identified, including memory CD4 T, NKT, NK, B, DC, CD8 T cells, and platelets. NK cells were significantly decreased in patients with AD, while CD4 T cells were increased. NK and DC cells exhibited the highest IRG activity. GO and KEGG analyses of the scRNA and bulk sequencing data showed that the DEGs focused on the immune response. Seventy common IRGs were found in both peripheral NK cells and the brain. Seventeen TFs were associated with IRG expression, and the PPI network indicated that STAT3, IRF1, and REL were the hub TFs. In conclusion, we propose that peripheral NK cells may infiltrate the brain and contribute to neuroinflammatory changes in AD through bioinformatic analysis of scRNA and bulk sequencing data. Moreover, STAT3 may be involved in the transcriptional regulation of IRGs in NK cells.